2016
DOI: 10.1016/j.molcata.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing C3–C4 alcohol synthesis pathways over a MgAl oxide supported K/MoS2 catalyst via 13C2-ethanol and 13C2-ethylene co-feeds

Abstract: Mechanisms of C 3-C 4 alcohol synthesis from syngas are elucidated over a Mg/Al mixed metal oxide (MMO) supported K/MoS 2 catalyst via 13 C 2-ethanol and 13 C 2-ethylene co-feeds. K/bulk-MoS 2 is used as a control catalyst to provide insight into the role of K/MoS 2 and K/MoS 2-MMO sites on higher alcohol formation pathways. Analysis of the products via 13 C-NMR show preferential enrichment of terminal carbons in C 3-C 4 alcohols with both co-feeds, suggesting that CO insertion is the primary higher alcohol sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, only a handful of catalysts that realize the catalytic Guerbet reaction of ethanol have been developed. Heterogeneous catalytic systems generally require harsh reaction conditions and/or suffer from low selectivity . In contrast, well-defined homogeneous catalysts based on precious metals (Ru and Ir) show higher reactivity and selectivity for this transformation under milder conditions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, only a handful of catalysts that realize the catalytic Guerbet reaction of ethanol have been developed. Heterogeneous catalytic systems generally require harsh reaction conditions and/or suffer from low selectivity . In contrast, well-defined homogeneous catalysts based on precious metals (Ru and Ir) show higher reactivity and selectivity for this transformation under milder conditions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the direct coupling of C 2 fragments is a probable source of additional C 4+ alcohols and hydrocarbons. Previous studies 13,35 on ethanol conversion using 13 C have shown that the coupling of C 2 fragments is involved in the formation of butanol (see in Table 3).…”
Section: Nsmentioning
confidence: 99%
“…Only small amounts of DEE were observed, which is a major product of ethanol conversion on a Bronsted acid catalyst. 35 This suggests that even in the absence of potassium, ethanol conversion, including dehydrations, proceeds on the Lewis acid sites of the sulfide catalyst, which are likely associated with CUS.…”
Section: Nsmentioning
confidence: 99%
“…Two chemical ways are worthy of note: a selective two-step approach coupling the formation of propylene via a standard MTO technology with hydroformylation/hydrogenation steps according to the alcohols OXO synthesis and a more challenging, rather unselective, route with the direct use of syngas to generate either methanol selectively or a broader range of so-called “higher” alcohols (HAS route). Among the numerous catalytic systems developed over the years, four main classes are noteworthy, being the focus of many valuable reviews: Rhodium-based catalysts producing mainly ethanol, modified FT catalysts based on cobalt and, to a lesser extent, iron, , MoS 2 /MoC-based catalysts, and optimized high- and low temperatures methanol catalysts based either on ZnO/Cr 2 O 3 or on the Cu/ZnO/Al 2 O 3 system often modified with alkali promoters (e.g., Cs and K). Although many of these four catalytic approaches have been further developed, some tested in pilot plants and/or patented, no large-scale industrial implementation has been so far reported. This might be explained by enduring problems associated with the stability of the catalysts, the exothermic character of the synthesis, and the moderate selectivity of the synthesis resulting in a broader product range (e.g., linear vs branched alcohol issue, oligomerization, etc.).…”
Section: Catalytic Chemical Route From Synthesis Gas To C4 Moleculesmentioning
confidence: 99%